SLIP OF THE TONGUE IN BARACK OBAMA INTERVIEW AT THE AXE FILE (PROJECT (Professional Journal of English Education), 2021)
This study examines the type of slip of the tongue in Barack Obama's interview at The Axe Files. It also analyzes the possible factors causing the error in speech production in the context of political discourse. It used Fromkin’s and Clark’s theories to investigate the audio data on The Axe File episode 108 and 288 published in 2016 and 2018. The result shows that Obama employed anticipation, perseveration, transposition, substitution, blend, and haplologies. The dominant type produced in the interview is substitution.  In addition, the factors influencing slip production are cognitive difficulty, situational anxiety, and social factors. These findings can be a reference for EFL teachers to show the various type of speech error produced in political discourses by native speakers. Further researchers are expected to use other relevant theories to classify a slip of the tongue in several other contexts.